Performances Assessment of Wastewater Treatment Plant in Boujaâd City, Khouribga Province, Morocco - Ouhamchich, Kamal Ait; Arioua, Abdelkrim; Lbayny, Mustapha; Karaoui, Ismail; Habbari, Khalid El; Idrissi, Abdelkhalek El Amrani; Hssaisoune, Mohamed; Boulli, Abdelali; Elhamdouni, Driss; Elfiraoui, Fatima Ezzahra (European Scientific Journal, ESJ, 2018)
The wastewater purification is a complicated and costlier operation if it not well chosen. Contrariwise, it could be simple and cheaper if the treatment system respect the environmental conditions and under international standards. To purify its wastewater, Boujaâd City chose to use the natural lagooning system. To verify the ability of this system, our study focuses on assessing the performances of this system to purify Boujaad city wastewater. For this reason, this study is based on the physicochemical monitoring of raw and purified water, both spatially and temporally, to detect and determine the percentage of pollution abatement in this wastewater treatment plant. According to the results, the quality of wastewater treatment plant rejection is conforming to the national and international standards. Here, the biochemical oxygen demand (BOD), chemical oxygen demand (COD), and suspended solids (SS) parameters reached 69%, 66%, and 86% respectively. The results obtained show that the purification operation in Boujaad wastewater treatment plant was adequate.